Testicular anti-müllerian hormone: Clinical applications in DSD - Josso, Nathalie (2012)
Male fetal sexual differentiation of the genitalia is driven by Leydig cell-secreted androgens and Sertoli cell-secreted anti-Müllerian hormone (AMH). Disorders of sex development (DSD) may be due to abnormal morphogenesis of genital primordia or to defective testicular hormone secretion or action. In dysgenetic DSD, due to an early fetal-onset primary hypogonadism affecting Leydig and Sertoli cells, the fetal gonads are incapable of producing normal levels of androgens and AMH. In non-dysgenetic DSD, either Leydig cells or Sertoli cells are affected but not both. Persistent Müllerian duct syndrome (PMDS) may result from Sertoli cell-specific dysfunction due to mutations in the AMH gene; these patients have Fallopian tubes and uterus, but male external genitalia. In DSD due to insensitivity to testicular hormones, fetal Leydig and Sertoli cell function is normal. Defective androgen action is associated with female or ambiguous genitalia whereas insensitivity to AMH results in PMDS with normal serum AMH. Clinical and biological features of PMDS due to mutations in the genes coding for AMH or the AMH receptor, as well as genetic aspects and clinical management are discussed. © 2012 by Thieme MedicalPublishers, Inc., 333 Seventh Avenue,New York, NY 10001, USA.